Foreword to the Special Issue on Uralic Languages - Tommi A Pirinen; Trond Trosterud; Francis M. Tyers; Veronika Vincze; Eszter Simon; Jack Rueter (Northern European Journal of Language Technology)
In this introduction we have tried to present concisely the history of language technology for Uralic languages up until today, and a bit of a desiderata from the point of view of why we organised this special issue. It is of course not possible to cover everything that has happened in a short introduction like this. We have attempted to cover the beginnings of the (Uralic) language-technology scene in 1980’s as far as it’s relevant to much of the current work, including the ones presented in this issue. We also go through the Uralic area by the main languages to survey on existing resources, to also form a systematic overview of what is missing. Finally we talk about some possible future directions on the pan-Uralic level of language technology management.